A case of chronic left main trunk occlusion treated with off-pump coronary artery bypass grafting. Issue 2 (13th February 2018) - Kawatani, Yohei; Nakamura, Yoshitsugu; Hori, Takaki
Abstract: Ischemic heart disease presents with various symptoms, and chest pain is a chief complaint. Occlusion of the left main trunk often results in serious symptoms such as cardiogenic shock. However, while extremely rare, left main trunk occlusion can present with only slight chronic symptoms. In the present case, a 62-year-old woman with few risk factors for ischemic heart disease visited our hospital complaining of exertional chest pain, which had gradually intensified over the past several years. Coronary artery computed tomography revealed total occlusion of the left main trunk, which was examined closely using coronary angiography. Coronary angiography showed that the left coronary artery was perfused by collateral pathways from the right coronary artery. The patient was thus diagnosed with chronic occlusion of the left main trunk. She underwent off-pump coronary artery bypass grafting, which proved to be an effective treatment.